2017
DOI: 10.1007/s10616-017-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of 2-dimensional culture for buffalo intestinal cells

Abstract: Small intestinal epithelial cells (IEC) play a major role in the absorption of nutrients and toxins. Due to the similarity of genome-wide single copy protein orthologues between cattle and human, establishment of ruminant's primary small IEC culture could be a valuable tool for toxicity studies. Therefore, the current study focused on the development and characterization of buffalo IEC culture, as cattle slaughter is banned in India. The buffalo jejunum fragments were washed consecutively several times in sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Cytokeratins are intermediate lament protein family members that are expressed as a network radiating from the nucleus to the plasma membrane. Cytokeratins are intracytoplasmic cytoskeleton proteins that are commonly used to identify (Giotakis et al, 2021;Chaudhary et al, 2018;Coch and Leube, 2016). Cytokeratins play an important role in protecting epithelial cells from mechanical and non-mechanical stressors (Karantza, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratins are intermediate lament protein family members that are expressed as a network radiating from the nucleus to the plasma membrane. Cytokeratins are intracytoplasmic cytoskeleton proteins that are commonly used to identify (Giotakis et al, 2021;Chaudhary et al, 2018;Coch and Leube, 2016). Cytokeratins play an important role in protecting epithelial cells from mechanical and non-mechanical stressors (Karantza, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the inability of BIEC-c4 cells to form tight junctions. The BIEC-c4 cells could be tested in further studies for the expression level of tight junction proteins (Anderson and Van Itallie 1995 ; Chaudhary et al 2018 ; McNeil et al 2006 ; Miyazawa et al 2010 ). In an earlier study, fetal-derived bovine duodenal epithelial cells not only showed high TEER values but also strongly expressed both zonula occludens-1 (ZO-1) and beta-catenin (Miyazawa et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine intestinal epithelial cell cultures have been established from the duodenum, jejunum, ileum, and colon of adult cattle and fetal calves (Birkner et al 2004 ; Kaushik et al 2008 ; Loret et al 2009 ; Rusu et al 2005 ; Yang et al 2015 ; Zhan et al 2017 ). Recently, intestinal epithelial cell culture established from the jejunum of buffalo has been reported (Chaudhary et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various fatty acid binding protein (FABP) isoforms, the fatty acid binding protein 2 (FABP2) is specific to the intestinal epithelium (Smathers and Petersen, 2011); thus, it can be considered a molecular biomarker of the small intestine (Thumser et al, 2014;Saqui-Salces et al, 2017;Chaudhary et al, 2018). Similar to FABP2, cytokeratins are proteins highly expressed in the epithelial cells.…”
Section: Short Communicationmentioning
confidence: 99%